Susceptibility‐based positive contrast MRI of brachytherapy seeds. Issue 3 (23rd September 2014) - Dong, Ying; Chang, Zheng; Xie, Guoxi; Whitehead, Gregory; Ji, Jim X.
<x xml:space="preserve">Abstract</x> Purpose To provide visualization of the brachytherapy seeds and differentiation with natural structures in MRI by taking advantage of their high magnetic susceptibility to generate positive‐contrast images. Methods The method is based on mapping the susceptibility using an equivalent short‐TE sequence and a kernel deconvolution algorithm with a regularized L1 minimization. An appealing aspect of the method is that signals from the surrounding areas where signal to noise ratio (SNR) is sufficiently high are used to derive the susceptibility of the seeds, even though the SNR in the immediate vicinity of the seeds can be extremely low due to rapid signal decay. Results The method is tested using computer simulations and experimental data. Comparing to conventional methods, the proposed method improves seed definition by a factor of >70% in the experiments. It produces the enhanced contrast at the exact seed location, whereas methods based on susceptibility gradient mapping produce highlighted regions surrounding the seeds. The proposed method is capable to perform the function for a wide range of resolutions and SNRs. Conclusion The results show that the proposed method provides positive contrast for the seeds and correctly differentiates them from other structures that appear similar to the seeds on conventional magnitude images. Magn Reson Med 74:716–726, 2015. © 2014 Wiley Periodicals, Inc.